2016
DOI: 10.1371/journal.pone.0147975
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Floral Perfumes Become Different? Region-Specific Selection on Floral Scent in a Terrestrial Orchid

Abstract: Geographically structured phenotypic selection can lead to adaptive divergence. However, in flowering plants, such divergent selection has rarely been shown, and selection on floral signals is generally little understood. In this study, we measured phenotypic selection on display size, floral color, and floral scent in four lowland and four mountain populations of the nectar-rewarding terrestrial orchid Gymnadenia odoratissima in two years. We also quantified population differences in these traits and pollinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
86
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 61 publications
5
86
3
3
Order By: Relevance
“…In particular, our results support the hypothesis that scent composition is either less constrained than flower shape and color (e.g., due to relative amounts of heritable variation), exposed to stronger selection (e.g., Gross et al. ), or both. Perhaps due in part to the technical aspects of its quantification, the evolution floral scent has traditionally received less attention in a phylogenetic framework compared to other floral traits, such as floral color and shape (e.g., Gómez et al.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, our results support the hypothesis that scent composition is either less constrained than flower shape and color (e.g., due to relative amounts of heritable variation), exposed to stronger selection (e.g., Gross et al. ), or both. Perhaps due in part to the technical aspects of its quantification, the evolution floral scent has traditionally received less attention in a phylogenetic framework compared to other floral traits, such as floral color and shape (e.g., Gómez et al.…”
Section: Discussionsupporting
confidence: 83%
“…Yet, species often have characteristic blends that can be detected even in the face of sources of substantive intraspecific variation (Gross et al. ). For example, recent studies in well‐sampled species of Zamia and Macrozamia showed high species specificity of scents despite variation among populations (Suinyuy et al.…”
Section: Discussionmentioning
confidence: 99%
“…More surprisingly, we observed selection for reduced nocturnal emission rates of indole and elemicin, two compounds that increase at night in this orchid species (Chapurlat et al ., ). The lack of congruence between diel patterns of scent emission and current net selection suggests that the observed difference in emission rate between day and night does not necessarily represent an equilibrium, or that there is temporal variation in selection on scent, as observed in a closely related species (Gross et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Given the multifunctional nature of linalool and the conflicting selective pressures brought to bear by floral mutualists and antagonists in response to its emission from flowers, this VOC would seem ideally suited to studies of geographic variation in phenotypic selection [58], in accordance with predictions of the Geographic Mosaic Theory of Coevolution, which outlines scenarios in which coevolutionary interactions should differ in the strength and direction of selection [59]. However, it should be clear from this review that linalool is not a special case, and we should expect most widespread floral volatiles to demonstrate a similar diversity of biological functions (see [4,20]).…”
Section: Discussionmentioning
confidence: 99%